Effect of Fe-doped TiO2 photocatalysts on the degradation of acid orange 7. Issue 168 (2nd January 2016) - Butler, Erick B.; Chen, Ching-Cheng; Hung, Yung-Tse; Al Ahmad, Mohammed Suleiman; Fu, Yen-Pei
ABSTRACT: The purpose of the research was to determine the photocatalytic degradation efficiency of acid orange 7 (AO7) using 2 mol% Fe-doped TiO2 as photocatalysts under UV irradiation. Fe-doped TiO2 powder synthesized by solid-reaction technique reveals the average particle size of 0.91 μm, BET surface area of 11.6 m 2 /g, a wide pore-size distribution with the average pore diameter of 3.2 nm and pore volume of 0.035 cm 3 /g. Within the experiment, AO7 was prepared as a synthetic textile wastewater at the initial concentration of 34 mg/L along with using various doses of Fe-doped TiO2 photocatalysts. The results indicated that Fe-doped TiO2 with dose of 0.100 g in 100 mL of AO7 reached the highest removal efficiency about 88.7%.